Analisis Perilaku Portal Beton Bertulang Dengan Tulangan Fibre Reinforced Polymer - Suriyati Suriyati; Ridwan Ridwan; Zulfikar Djauhari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Fiber reinforcement is currently widely used as an alternative to conventional steel reinforcement at reinforced concrete because its material properties are resistant to corrosion and have a high tensile strength. This research aims to analyze the comparison of reinforced concrete portal behavior using FRP and steel reinforcement. The model used in the analyzed is portal 2D with and without shear wall that use limits of based on ACI 440.1R-2015 and SNI 03-2847-2013. The analyzed result revealed that the use of FRP bar can reduce the amount of bars significantly. For the case of concrete portal without shear wall was 25% less than compared to that FRP of steel bars. Moreover, for the case of portal with shear wall, the use of FRP material can reduce the amount at bars used until 33%. This can be inferred because ultimate strength and modulus elasticity of CFRP is 2070 MPa and 152000 MPa, while ultimate strength of conventional steel is only MPa with the modulus of elasticity of 200000 MPa. Keywords: Reinforcement FRP, Conventional Steel Reinforcement, Reinforcement CFRP